2020
DOI: 10.1002/gps.5325
|View full text |Cite
|
Sign up to set email alerts
|

What are the psychosocial consequences when fear of falling starts or ends? Evidence from an asymmetric fixed effects analysis based on longitudinal data from the general population

Abstract: The purpose of this study was to identify whether the onset and the end of fear of falling (FOF) are associated with psychosocial consequences (in terms of depressive symptoms, loneliness, social isolation, autonomy, and subjective wellbeing). Methods/Design: Longitudinal data for this study were taken from the nationally representative German Ageing Survey which included community-dwelling individuals ≥40 years (wave 5 and wave 6). Psychosocial outcome measures were assessed using widely established and well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…FOF is a common psychological concern among older adults, affecting approximately a third of those who have fallen and nearly 50% of older adults who have not experienced a fall [ 20 ]. FOF is associated with negative health outcomes such as decreased physical and cognitive functioning, decreased mental health and well-being [ 21 , 22 ], increased symptoms of depression, frequent experiences of loneliness [ 23 ], and poor quality of life [ 24 ]. FOF can also result in limitations in physical activity related to daily life [ 25 ] and avoidance of physical and social activities [ 21 ], even in individuals without a history of falls [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…FOF is a common psychological concern among older adults, affecting approximately a third of those who have fallen and nearly 50% of older adults who have not experienced a fall [ 20 ]. FOF is associated with negative health outcomes such as decreased physical and cognitive functioning, decreased mental health and well-being [ 21 , 22 ], increased symptoms of depression, frequent experiences of loneliness [ 23 ], and poor quality of life [ 24 ]. FOF can also result in limitations in physical activity related to daily life [ 25 ] and avoidance of physical and social activities [ 21 ], even in individuals without a history of falls [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear of falling is related to adverse health events such as increased depressive symptoms [11], reduction in physical activity [5], functional decline [12], and increased risk of falls [13]. Several conditions can predispose a person to fear of falling, among which are female sex [14,15], a negative health self-perception [16,17], environmental factors such as residing near garbage accumulation and/or open sewers and high crime rates [10], the presence of cognitive decline [4,7], and multimorbidity [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…To date, various previous studies have identified socioeconomic and health-related correlates of psychosocial outcomes in the general adult population and in later life. 3,4 However, there is limited knowledge regarding these associations exclusively among the oldest old. [5][6][7] Therefore, our aim was to clarify the determinants of psychosocial outcomes among the oldest old in Germany.…”
Section: Introductionmentioning
confidence: 99%